Tire

By optimizing the design of the sidewall rubber composition and bead triangle glue, combined with filler and micro-bulge structure, the problem of insufficient crack resistance of the tire sidewall is solved, achieving higher durability and low fuel consumption performance.

CN119175966APending Publication Date: 2024-12-24SUMITOMO RUBBER INDUSTRIES LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410745685.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-11
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing tires have shortcomings in crack resistance and longevity of sidewalls, especially in the context of improved environmental load and fuel consumption performance, there is still room for improvement in crack resistance of sidewalls.

Method used

Develop specific relationships by optimizing the loss tangent (tanδ) and complex elastic modulus (E*) of the sidewall rubber composition, combining the appropriate amount of bead triangular height and the use of fillers such as silica and carbon black to improve crack resistance of the sidewall walls and to form multiple tiny bulges on the outer surface to reduce stress concentration.

Benefits of technology

It significantly improves the crack resistance and durability of the sidewall, extends the service life of the tire, and reduces fuel consumption and environmental load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119175966A_ABST
    Figure CN119175966A_ABST
Patent Text Reader

Abstract

The present application provides a tire in which the crack resistance of a sidewall is improved. A tire which is provided with a pair of sidewalls and a pair of bead apex, and which is characterized in that: the loss tangent (tan [delta]) of a rubber composition constituting the sidewalls at 70 DEG C is 70 DEG C tan [delta], the complex elastic modulus (MPa) of the rubber composition at 70 DEG C is 70 DEG C E *, the height (mm) of the bead apex is H, the tire weight (kg) of the tire is G, when the maximum load capacity (kg) of the tire is WL, 70 DEG C tan [delta], 70 tan, H, G, and WL satisfy the following relationship. (1) 0.006 * H-70 DEG C tan [delta] gt; 0.320 (2) 70 DEG C E * lt; 10.0 (3) G / WLlt; and 0.0180 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a tire. Background Art

[0002] At present, the requirements for the fuel efficiency of tires are increasing day by day. In order to improve the fuel efficiency of tires, not only the tread of the tire but also other parts such as the sidewall are being studied to reduce fuel consumption. For example, Patent Document 1 describes that the fuel efficiency is improved by using a rubber composition containing a specified resin in the sidewall of the tire. [Prior art literature] [Patent Literature]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 2021-14506 Summary of the invention [Problems to be solved by the invention]

[0004] On the other hand, from the viewpoint of reducing environmental load, etc., there is a demand for further extending the life of tires, and there is still room for improvement in terms of improving the crack resistance of the sidewall and further extending the life.

[0005] An object of the present invention is to improve the crack resistance of a sidewall.

Methods to solve the problem

[0006] The present invention relates to the following tire. A tire having a pair of sidewalls and a pair of bead apex rubbers. Assuming that the loss tangent (tanδ) of the rubber composition constituting the sidewall at 70°C is 70°C tanδ, the complex elastic modulus (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex rubber is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) of the tire is WL, 70°C tanδ, 70°C E*, H, G and WL satisfy the following relationship. (1) 0.006×H-70℃tanδ>0.320 (2) 70℃E*<10.0 (3)G / WL<0.0180 [Effects of the invention]

[0007] According to the present invention, it is possible to improve the crack resistance of the sidewall. BRIEF DESCRIPTION OF THE DRAWINGS

[0008]

Figure 1

Figure 2

Figure 3

Figure 4

Figure 5

Figure 6

Figure 7

[0009] The present invention relates to the following tire. A tire having a pair of sidewalls and a pair of bead apex rubbers. Assuming that the loss tangent (tanδ) of the rubber composition constituting the sidewall at 70°C is 70°C tanδ, the complex elastic modulus (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex rubber is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) of the tire is WL, 70°C tanδ, 70°C E*, H, G and WL satisfy the following relationship. (1) 0.006×H-70℃tanδ>0.320 (2) 70℃E*<10.0 (3)G / WL<0.0180

[0010] Although not wishing to be bound by theory, in the present invention, the mechanism that can improve the crack resistance of the sidewall is considered to be as follows. That is, since the sidewall deforms when the tire rotates, cracks are likely to occur due to the accumulation of deformation from driving. In contrast, in the tire of the present invention, (A) as shown in the above formula (1), the loss tangent tanδ of the sidewall is adjusted according to the height of the bead apex. It is believed that: when the tanδ of the sidewall is high, the rubber becomes easy to break due to the heat generated during rotation, and cracks become easy to occur, but by having a sufficient height of the bead apex, the deformation is suppressed and the heat generation can also be reduced. On the other hand, it is believed that when the height of the bead apex is low, the loss tangent tanδ of the sidewall rubber becomes smaller, the heat generation is suppressed, and it helps to suppress cracks. In addition, it is believed that: (B) as shown in the above formula (2), since the complex elastic modulus 70℃E* of the sidewall rubber is soft below the specified value, it can be flexibly deformed relative to the strain occurring on the surface, which helps to suppress cracks. Furthermore, (C) as in the above formula (3), the maximum load capacity relative to the tire weight is increased. The maximum load capacity of the tire is a value proportional to the volume of the tire. It is believed that by increasing the maximum load capacity relative to the tire weight, the thickness of the tire as a whole becomes thinner, which can improve the heat dissipation effect. Moreover, it is believed that: through the synergistic effect of these (A) to (C), while suppressing the heat generation and heat storage of the sidewall portion, the softness of the sidewall rubber surface is ensured, and the state of high fracture resistance is maintained, thereby improving the crack resistance of the sidewall.

[0011] When the thickness of the sidewall at the maximum width position of the tire is T (mm), 70°C E* and T preferably satisfy the following relationship. (4) 70℃E*×T<31.5

[0012] Since the 70°C lower E* can increase the flexibility of the rubber, it deforms softly during deformation, making it easier to suppress the occurrence of cracks. Furthermore, by making the thickness of the sidewall thinner, the volume of the rubber is reduced, the heat generation is reduced, and the temperature rise of the sidewall can be suppressed, making it easier to suppress the occurrence of cracks. Therefore, it is believed that by satisfying the relationship of formula (4), the softness during deformation and the reduction of heat generation are interrelated, and the crack resistance of the sidewall is improved.

[0013] The rubber composition preferably contains silica.

[0014] It is believed that by mixing a small amount of silica, the rubber is appropriately reinforced, the silica surfaces become easier to slide against each other, and the elongation at break (EB) is improved. In addition, it is believed that by improving the EB, cracking during large deformation is suppressed, and the crack resistance of the sidewall is improved.

[0015] The rubber composition preferably contains carbon black, and the carbon black contains recovered carbon black (rCB).

[0016] Since the surface of rCB is incinerated, the bonding with the surrounding rubber molecules tends to be slightly weaker. Therefore, the surrounding rubber molecular chains become more likely to release force when deformed, and the crack resistance of the sidewall is improved.

[0017] The rubber composition preferably contains silica and carbon black. When the content (parts by mass) of the silica is S and the content (parts by mass) of the carbon black is C relative to 100 parts by mass of the rubber component, S and C preferably satisfy the following relationship. (5)S / C>0.50

[0018] It is considered that by making the blending amount of silica greater than half the blending amount of carbon black, the effect of improving the elongation at break due to silica can be obtained, and the rubber composition can be easily reinforced, thereby easily improving the crack resistance.

[0019] The rubber composition preferably contains silica and carbon black, and the carbon black contains recycled carbon black. Relative to 100 parts by mass of rubber, when the content (parts by mass) of the silica is S and the content (parts by mass) of the recycled carbon black is rC, S and rC preferably satisfy the following relationship. (6)S / rC>1.00

[0020] It is considered that by making the blending amount of silica larger than the blending amount of carbon black, the effect of improving the elongation at break due to silica and the effect of dispersing the force due to rCB can be easily obtained.

[0021] At least one of the pair of sidewalls preferably has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface.

[0022] It is considered that the presence of the micro-protrusion forming portion can suppress stress concentration on the outer surface of the sidewall, thereby contributing to improving the crack resistance of the sidewall.

[0023] The shape of the micro protrusions is preferably columnar, frustum-shaped or rib-shaped.

[0024] It is considered that the micro-protrusions having the prescribed shapes can suppress stress concentration on the outer surface of the sidewall, thereby contributing to improving the crack resistance of the sidewall.

[0025] The height of the micro-ridges is 0.03 mm or more and 0.50 mm or less, and 20 or more micro-ridges are formed at intervals of 0.50 mm or less in at least one direction. The micro-ridge forming portion preferably has a width of 10 mm. 2 The area above.

[0026] It is considered that by setting the size of the micro-ridges within the prescribed range, stress concentration on the outer surface of the sidewall can be suppressed, thereby contributing to improving the crack resistance of the sidewall.

[0027] The microridges preferably have a maximum width of not less than 0.03 mm and not more than 5.0 mm.

[0028] It is considered that by setting the maximum width of the micro-ridges within a predetermined range, stress concentration on the outer surface of the sidewall can be suppressed, thereby contributing to improving the crack resistance of the sidewall.

[0029] The height of the micro-ridges preferably increases gradually from the maximum width position of the tire toward the outer side in the tire radial direction, and also increases gradually from the maximum width position of the tire toward the inner side in the tire radial direction.

[0030] It is believed that although relatively large strain occurs near the maximum width position of the tire on the sidewall, by making the height of the tiny ridges lower as they are closer to the maximum width position of the tire, the unevenness of the rubber volume in the circumferential direction of the tire at the position where the large strain occurs is reduced, avoiding stress concentration near the tiny ridges, which helps to improve the crack resistance of the sidewall.

[0031] <Definition> The “normal state” refers to an unloaded state in which the tire is assembled on a normal rim and filled with a normal internal pressure. Unless otherwise specified, the “dimensions of various parts of the tire” are set to values ​​determined in the normal state.

[0032] "Regular rim" means: in the specification system including the specification on which the tire is based, the rim specified for each tire in the specification, in the case of JATMA (Japan Automobile Tire Association), it is the standard rim in the applicable size listed in the "JATMA YEAR BOOK", in the case of ETRTO (The European Tyre and Rim Technical Organisation), it is the "Measuring Rim" listed in the "STANDARDS MANUAL", and in the case of TRA (The Tire and Rim Association, Inc.), it is the "Design Rim" listed in the "YEAR BOOK", and JATMA, ETRTO, and TRA are referred to in this order, and when referring to applicable sizes, the applicable sizes are followed. In addition, in the case of a tire not specified in the above specification system, it means a rim that can be assembled on the tire and can maintain the internal pressure, that is, a rim with the smallest diameter and the narrowest rim width among the rims that will not cause air leakage from the rim / tire.

[0033] "Normal internal pressure" means: in the specification system including the specifications on which the tire is based, the air pressure specified for each tire in each specification. If it is JATMA, it is the "maximum air pressure", if it is ETRTO, it is the "inflation pressure (INFLATIONPRESSURE)", and if it is TRA, it is the maximum value recorded in the table "Tire load limits at various cold inflation pressures (TIRE LOAD LIMITS ATVARIOUS COLD INFLATION PRESSURES)". Like regular rims, they are referenced in the order of JATMA, ETRTO, and TRA. When referencing, if there is an applicable size, its specifications are followed. In addition, in the case of a tire not specified in the specification, it refers to the normal internal pressure (of which 250KPa or more) of other tire sizes (specified in the specification) recorded with the above-mentioned normal rim as the standard rim. In addition, when there are multiple normal internal pressures of more than 250KPa, it refers to the minimum value among them.

[0034] "Height (H) (mm) of the bead apex" refers to: the distance from the lower end of the bead apex to the upper end of the bead apex in the tire cross section including the tire rotation axis. Here, the lower end of the bead apex refers to the upper end of the bead core, and the upper end of the bead apex refers to the outermost point of the bead apex in the tire radial direction. Among them, when a bead reinforcement layer exists, the upper end of the bead apex is the outermost point of the bead reinforcement layer in the tire radial direction. The bead reinforcement layer refers to: a layer that reinforces the bead portion arranged on the outer side of the tire width direction of the rolled-up portion of the tire body that rolls up the bead portion from the inner side to the outer side in the tire width direction.

[0035] “Tire weight (G) (kg)” refers to the weight of the tire alone excluding the weight of the rim. When noise suppression materials, sealing layers, sensors, etc. are installed in the tire cavity, G is a value including the weight of these.

[0036] "Maximum load capacity (WL) (kg)" is the value calculated by the following formula (A) and formula (B) when the tire cross-section width measured under normal conditions is Wt (mm), the tire cross-section height is Ht (mm), and the tire outer diameter is Dt (mm). V is the virtual volume of the space occupied by the tire. The above tire cross-section width Wt is the maximum width between the outer sides of the sidewall after removing the patterns or text on the side of the tire under normal conditions. The above tire cross-section height Ht is the distance from the bottom surface of the bead to the outermost surface of the tread (tread), which is 1 / 2 of the difference between the tire outer diameter Dt and the rim diameter R (mm). V = {(Dt / 2) 2 -(Dt / 2-Ht) 2}×π×Wt……(A) WL=0.000011×V+100……(B)

[0037] "Sidewall thickness (T) (mm)" refers to the thickness (mm) of the rubber constituting the sidewall measured at the tire maximum width position PW of the sidewall on the normal line L to the tire surface. "Tire maximum width position PW" refers to the position on the sidewall surface where the tire cross-sectional width Wt is measured.

[0038] The "micro-ridge" refers to a convex ridge formed on the outer surface of the sidewall and having a height of 0.03 mm or more and 5.0 mm or less. The micro-ridge preferably has a maximum width of 0.03 mm or more and 5.0 mm or less.

[0039] The "micro-ridge formed portion" refers to a portion on the outer surface of the sidewall where the micro-ridge is formed.

[0040] "Recovered carbon black" refers to carbon black obtained from the thermal decomposition process of used tires and other products containing carbon black, and refers to carbon black whose mass ratio of ash as non-combustible components (ash content) is 13% by mass or more when heated in air for oxidative combustion by the thermogravimetric method of JIS K 6226-2:2003. In other words, the mass (carbon content) of the reduced part by oxidative combustion is 87% by mass or less. Recovered carbon black is sometimes also represented by rCB.

[0041] The "content of plasticizer" also includes the amount of plasticizer in the rubber component extended by the plasticizer. Similarly, the "content of oil" also includes the amount of oil contained in the oil-extended rubber.

[0042] <Measurement method> Styrene content 1 The results were obtained by H-NMR measurement and calculation.

[0043] The "vinyl bond amount (1,2-bonded butadiene unit amount)" is measured by infrared absorption spectroscopic analysis.

[0044] The cis content (amount of cis-1,4-bonded butadiene units) was measured by infrared absorption spectroscopic analysis.

[0045] The “weight average molecular weight (Mw)” can be determined by converting the measured value using gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMALTPORE HZ-M manufactured by Tosoh Corporation) by standard polystyrene conversion.

[0046] "Carbon Black N 2 "SA" is a value obtained in accordance with JIS K 6217-2:2017.

[0047] "Silica N 2 "SA" is a value measured by the BET method according to ASTM D3037-93.

[0048] The "average primary particle size" is the value obtained by taking a picture of the particles with a transmission or scanning electron microscope and calculating the arithmetic mean of 400 particle sizes. Regarding the particle size, when the particle shape is roughly circular, the diameter of the circle is the particle size, and when it is needle-shaped or rod-shaped, the short diameter is the particle size. In other cases, the equivalent circle diameter is calculated from the electron microscope image as the particle size. The equivalent circle diameter can be calculated as "4×(area of ​​the particle) / π square root". This applies to silica and carbon black, etc.

[0049] Unless otherwise specified, the “softening point of a resin or the like” is the temperature at which a ball falls when the softening point specified in JIS K6220-1:2015 is measured using a ring and ball softening point measuring apparatus. Softening points measured by other methods will be specified.

[0050] "70°C tanδ" is measured using the Eplex series manufactured by GABO under the conditions of temperature 70°C, initial strain 10%, dynamic strain ±1%, frequency 10 Hz, and tensile mode. When sampling from the tire, a sample of 20 mm long × 4 mm wide × 1 mm thick was taken from the rubber layer inside the sidewall of each test tire, with the tangent direction of the tire circumferential direction as the long side and the tire width direction as the thickness.

[0051] "70°C E*" is the complex elastic modulus (MPa) measured using the Eplex series manufactured by GABO under the conditions of temperature 70°C, initial strain 10%, dynamic strain ±1%, frequency 10 Hz, and tensile mode. When sampling from the tire, the same measurement as for 70°C tanδ is performed.

[0052] <Tires> The tire of the present invention is described below with reference to the accompanying drawings, which are merely examples for illustration.

[0053] The tire of the present invention is a tire in which the 70°C tanδ of the rubber composition constituting the sidewall, the 70°C E* of the above-mentioned rubber composition, the height (mm) H of the bead apex rubber, the tire weight (kg) G, and the maximum load capacity (kg) WL of the tire satisfy the prescribed relationships represented by the above-mentioned formula (1), the above-mentioned formula (2), and the above-mentioned formula (3).

[0054] Figure 1 It is a cross-sectional view of a tire having a pair of sidewalls and a pair of bead apex rubbers, taken through a plane passing through the tire's axis of rotation. Figure 1 In the figure, the height of the bead apex (Ba) is represented by H, which is the distance from the upper end of the bead core (Bc) which is the lower end of the bead apex (Ba) to the outermost point in the tire radial direction of the bead apex which is the upper end of the bead apex (Ba). Figure 2 The case where the bead portion has a bead reinforcement layer (Br) is shown. The bead reinforcement layer (Br) refers to: a layer that reinforces the bead portion on the outside of the tire width direction of the rolled portion of the carcass (Cc) that is rolled around the bead portion from the inside to the outside in the tire width direction. In this case, the lower end of the bead apex rubber refers to the upper end of the bead core (Bc), and the upper end of the bead apex rubber refers to the outermost point of the bead reinforcement layer in the tire radial direction. In addition, Figure 1 and Figure 2 The tire section width Wt, tire section height Ht, and tire outer diameter Dt (mm) required to calculate the tire's maximum load capacity (WL) are shown.

[0055] (Formula (1)) The relationship satisfied by formula (1) is as follows. (1) 0.006×H-70℃tanδ>0.320

[0056] The value of the right side of formula (1) is preferably 0.323, more preferably 0.328, further preferably 0.329, further preferably 0.333, further preferably 0.339. The upper limit of the value of the left side of formula (1) is not particularly limited from the viewpoint of the effect of the present invention, and is, for example, 0.600.

[0057] Although H varies depending on the size of the tire, it is usually 50 mm or more, preferably 55 mm or more, and more preferably 60 mm or more. In addition, from the viewpoint of the effect of the present invention, H is not particularly limited, and is, for example, 110 mm.

[0058] The tanδ at 70°C is preferably less than 0.120, more preferably less than 0.110, further preferably less than 0.100, and further preferably less than 0.090. The lower limit of the tanδ at 70°C is not particularly limited from the viewpoint of the effect of the invention, but is, for example, preferably 0.020 or more, more preferably 0.030 or more, and further preferably 0.050 or more.

[0059] The 70°C tanδ of the rubber composition can be appropriately adjusted according to the types and mixing amounts of the components constituting the rubber composition described below. For example, the 70°C tanδ can be increased by increasing the amount of filler, reducing the particle size of the filler, reducing the amount of the vulcanizer and the vulcanization accelerator, etc. Therefore, the 70°C tanδ can be reduced by the reverse operation.

[0060] (Formula (2)) The relationship satisfied by formula (2) is as follows. (2) 70℃E*<10.0

[0061] The value on the right side of formula (2) is preferably 9.0, more preferably 8.0, further preferably 7.0, further preferably 6.0, further preferably 5.5, further preferably 4.5, further preferably 4.0, further preferably 3.8, further preferably 3.5, further preferably 3.0. The lower limit of the value on the left side of formula (2) is not particularly limited from the viewpoint of the effect of the present invention, and is, for example, 2.0.

[0062] The 70°C E* of the rubber composition can be appropriately adjusted according to the types and mixing amounts of the components constituting the rubber composition described below. For example, by increasing the amount of filler, reducing the particle size, reducing the total amount of plasticizer, and increasing the amount of vulcanizer and vulcanization accelerator, the 70°C E* tends to be increased. Therefore, by reverse operation, the 70°C E* tends to be reduced.

[0063] (Formula (3)) The relationship satisfied by formula (3) is as follows. (3)G / WL<0.0180

[0064] The tire of the present invention that satisfies the above formula (3) is a tire with a relatively large maximum load capacity relative to the tire weight. The value on the right side of formula (3) is preferably 0.0170, more preferably 0.0165, and further preferably 0.0161. On the other hand, the lower limit of G / WL is not particularly limited from the perspective of the effect of the present invention, and is, for example, 0.0120.

[0065] The value of G / WL can be reduced by reducing the relative value of G with respect to the value of WL, and conversely can be increased by increasing the relative value of G with respect to the value of WL.

[0066] As described above, WL is a value determined based on the tire cross-sectional width Wt (mm), the tire cross-sectional height Ht (mm), and the tire outer diameter Dt (mm). Figure 1 or Figure 2 Wt, Ht, and Dt of the tire are shown.

[0067] (Formula (4)) In the tire of the present invention, the above-mentioned 70° C. E* and the thickness T (mm) of the sidewall at the maximum width position of the tire preferably satisfy the following relationship. (4) 70℃E*×T<31.5

[0068] The value on the right side of formula (4) is preferably 25.0, more preferably 20.0, further preferably 16.0, further preferably 15.0, further preferably 14.0, further preferably 13.0, further preferably 12.0. The lower limit of the value on the left side of formula (4) is not particularly limited from the viewpoint of the effect of the present invention, and is, for example, 10.0.

[0069] like Figure 1 As shown, the thickness T of the sidewall is the thickness of the rubber constituting the sidewall measured along the normal line L of the tire maximum width position PW of the sidewall. Here, the tire maximum width position PW refers to the position on the outer surface of the sidewall where the tire cross-sectional width Wt is measured.

[0070] The thickness T (mm) of the sidewall is not particularly limited as long as it is within the generally applicable thickness range. For example, in the case of a tire for a passenger car, T is preferably greater than 1.0 mm, more preferably greater than 1.5 mm, further preferably greater than 2.0 mm, and further preferably greater than 3.0 mm. On the other hand, T is preferably less than 10.0 mm, more preferably less than 9.5 mm, further preferably less than 9.0 mm, further preferably less than 8.5 mm, and further preferably less than 8.0 mm.

[0071] (Micro-ridge formation area) The tire of the present invention preferably has a micro-ridge forming portion in which a plurality of micro-ridges are formed on an outer surface of at least one of the pair of sidewalls.

[0072] In the micro-ridge forming portion, the micro-ridges may be arranged in one row or in multiple rows in the radial direction of the tire. Here, one row in the radial direction of the tire means that there are not more than two micro-ridges arranged in the radial direction of the tire. In addition, the micro-ridges may be arranged in one row or in multiple rows in the circumferential direction of the tire. Here, one row in the circumferential direction of the tire means that there are not more than two micro-ridges arranged in the circumferential direction of the tire. Preferably, the micro-ridges are arranged in multiple rows in the radial direction of the tire and in multiple rows in the circumferential direction of the tire.

[0073] In the micro-ridge formation part, the area is the area defined by the line surrounding the outermost part of a plurality of micro-ridges arranged at intervals of 0.50 mm or less when viewed from a direction perpendicular to the surface of the tire. The area of ​​the micro-ridge formation part is preferably 10 mm 2 The above. Because it helps to suppress the stress concentration on the outer surface of the sidewall and improve the crack resistance of the sidewall. In addition, in the micro-protrusion forming portion, the whole formed by the micro-protrusions can be continuous or separated. Here, separated means that the interval between the micro-protrusions is greater than 1.0 mm. Therefore, the micro-protrusion forming portion only needs to have at least one on the outer surface of at least one of the pair of sidewalls, and can also have multiple.

[0074] (Slight bulge) The shape of the micro-protrusion is not particularly limited as long as it helps to suppress stress concentration on the outer surface of the sidewall and improve the crack resistance of the sidewall. Specifically, columnar, truncated cone, rib (strip) and the like can be cited. As a columnar shape, it includes not only a cylindrical shape but also a polygonal columnar shape such as a square column and a pentagonal column. As a truncated cone shape, it includes not only a circular truncated cone shape but also a polygonal truncated cone shape such as a triangular truncated cone shape, a square truncated cone shape, a pentagonal truncated cone shape. As a rib, the shape of the cross section perpendicular to the long direction of the micro-protrusion is not particularly limited and can include any type. As the shape of the cross section, for example, a rectangle or a trapezoid can be cited.

[0075] Figure 3 A part of a micro-ridge forming portion in which cylindrical micro-ridges 2 are formed on the outer surface 1 of the tire sidewall is shown. Figure 4 A part of a micro-ridge forming portion in which quadrangular pyramid-shaped micro-ridges 3 are formed on the sidewall outer surface 1 is shown. Figure 5 yes Figure 4 The XX cross-sectional view is a view of the micro-ridge observed from a direction perpendicular to a plane including a normal line standing on the outer surface of the tire sidewall. Figure 5The height h of the micro-ridges 3 , the maximum width w of the micro-ridges 3 , and the interval d between the micro-ridges 3 are shown. Figure 6 A part of a micro-ridge forming portion in which rib-shaped micro-ridges 4 are formed on the sidewall outer surface 1 is shown. Figure 7 yes Figure 6 The YY cross-sectional view is a view of the micro-ridge observed from a direction perpendicular to a plane including a normal line standing on the outer surface of the tire sidewall. Figure 7 The height h of the micro-ridges 4 , the maximum width w of the micro-ridges 4 , and the interval d between the micro-ridges 4 are shown.

[0076] Here, regarding the micro-ridge, "height" refers to the maximum height of the micro-ridge measured along the normal line standing on the outer surface of the sidewall, "maximum width" refers to the maximum width of the micro-ridge on the outer surface of the sidewall measured in one direction of the arrangement of the micro-ridges, and "interval" refers to the minimum interval of the micro-ridge on the outer surface of the sidewall measured in one direction of the arrangement of the micro-ridges. In addition, the height, maximum width, and interval of the micro-ridge are all measured when the outer surface of the sidewall is unfolded on a plane.

[0077] The height of the micro-ridges at the maximum width position of the tire is preferably 0.03mm or more, and may be 0.05mm or more, or 0.10mm or more. On the other hand, the height is preferably 0.50mm or less, 0.45mm or less, or 0.40mm or less. In addition, the maximum width of the micro-ridges is preferably 0.03mm or more, 0.05mm or more, or 0.10mm or more. On the other hand, the maximum width is preferably 5.00mm or less, 3.00mm or less, 1.00mm or less, or 0.50mm or less. Furthermore, the intervals between the micro-ridges are preferably 1.00mm or less, 0.70mm or less, 0.50mm or less, 0.30mm or less, 0.10mm or less, or 0.05mm or less. In addition, the intervals between the micro-ridges only need to be at least half of the maximum width, or the same as the maximum width. In addition, the density of the micro-ridges (number / cm 2 ) can be calculated from the maximum width and spacing of the above-mentioned micro-ridges. For example, in the following embodiment, about 700 / cm 2 .

[0078] Preferably, 20 or more micro-ridges are formed in at least one direction, because they can suppress stress concentration on the outer surface of the sidewall and contribute to improving the crack resistance of the sidewall.

[0079] The height of the micro-ridges is preferably increased gradually from the maximum width position of the tire toward the outer side of the tire radial direction, and from the maximum width position of the tire toward the inner side of the tire radial direction. This is because it is believed that a relatively large strain is generated near the maximum width position of the tire sidewall, but by making the height of the micro-ridges lower as they are closer to the maximum width position of the tire, the unevenness of the rubber volume in the tire circumferential direction at the position where a large strain is generated can be reduced, and stress concentration near the micro-ridges can be avoided, which helps to improve the crack resistance of the sidewall.

[0080] The micro-protrusions are preferably Figure 6 The micro-protrusion 4 shown in the figure has a concave portion on the arc on the outermost surface of the micro-protrusion. By adopting such a structure, air can be suppressed from accumulating in the arc-shaped concave portion, and the appearance defect of the micro-protrusion can be suppressed.

[0081] <Rubber Composition> The rubber composition constituting the sidewall of the tire of the present invention is described below. The rubber composition contains a rubber component and a filler, and may further contain other compounding agents.

[0082] (Rubber component) The rubber component preferably contains at least one rubber component selected from the group consisting of isoprene rubber (IR rubber), styrene-butadiene rubber (SBR) and butadiene rubber (BR). In addition, the rubber component may also contain at least two rubber components selected from the group consisting of IR rubber, SBR and BR, or may contain IR rubber, SBR and BR. Among them, the rubber component preferably contains IR rubber and BR. In addition, these rubber components may also be expanded rubbers increased by the following plasticizers, or may be hydrogenated rubber components subjected to modification treatment or hydrogenation on double bonds.

[0083] <<Isoprene rubber>> As isoprene-based rubber, natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, modified IR, etc. can be listed. As NR, for example, SIR20, RSS#3, TSR20 and other commonly used materials in the tire industry can be used. As IR, there is no particular limitation, and for example, R2200 and other commonly used materials in the tire industry can be used. As modified NR, deproteinized natural rubber (DPNR), high purity natural rubber (UPNR) and the like can be listed, as modified NR, epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), grafted natural rubber and the like can be listed, as modified IR, epoxidized isoprene rubber, hydrogenated isoprene rubber, grafted isoprene rubber and the like can be listed. These can be used alone, or two or more can be used in combination.

[0084] From the viewpoint of increasing the elongation at break of the rubber composition and improving the crack resistance, the content of the isoprene-based rubber in 100% by mass of the rubber component is preferably greater than 20% by mass, more preferably greater than 30% by mass, further preferably greater than 40% by mass, and further preferably 45% by mass or more. On the other hand, from the viewpoint of suppressing thermal deterioration, it is preferably less than 75% by mass, more preferably less than 65% by mass, and further preferably less than 55% by mass.

[0085] < <sbr>> As SBR, there is no particular limitation, for example, emulsion polymerization styrene-butadiene rubber (E-SBR), solution polymerization styrene-butadiene rubber (S-SBR) etc. can be used. In addition, as SBR, it can be non-modified SBR or modified SBR. In addition, SBR can also use hydrogenated styrene-butadiene copolymer (hydrogenated SBR). These can be used alone, or two or more can be used in combination.

[0086] The styrene content of SBR is preferably greater than 5.0% by mass, more preferably greater than 7.5% by mass, and further preferably greater than 10.0% by mass. The styrene content is preferably less than 40.0% by mass, more preferably less than 35.0% by mass, and further preferably less than 30.0% by mass. It is believed that by being within the above range, microscopic styrene domains can be formed in the rubber component, and strain caused by deformation can be easily absorbed in the rubber composition. In addition, in this specification, the styrene content can be expressed by 1 H-NMR determination.

[0087] The vinyl bonding amount of SBR is preferably greater than 5 mol%, more preferably greater than 10 mol%, and further preferably greater than 15 mol%. The vinyl bonding amount is preferably less than 65 mol%, more preferably less than 60 mol%, and further preferably less than 50 mol%. In addition, the vinyl bonding amount can be measured by the above method.

[0088] As SBR, SBR (volume-increasing SBR) that has been increased in volume by a plasticizer may be used, or non-volume-increasing SBR may be used. When volume-increasing BR is used, the volume increase of SBR, i.e., the content of the volume-increasing plasticizer contained in SBR, is preferably 10 to 50 parts by mass relative to 100 parts by mass of the rubber solid component of SBR. As the plasticizer used for increasing the volume, the following resins, oils, liquid polymers, ester plasticizers, etc. may be cited.

[0089] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Co., Ltd., etc. can be used.

[0090] The content of SBR in 100% by mass of the rubber component may be 0% by mass, for example, may be greater than 1% by mass, may be greater than 5% by mass, or may be greater than 10% by mass. The upper limit of the content of SBR is preferably less than 40% by mass, more preferably less than 35% by mass, and further preferably less than 30% by mass.

[0091] < > BR is not particularly limited, and examples thereof include high cis BR with a high cis content, BR containing syndiotactic polybutadiene crystals, BR synthesized using a rare earth catalyst (rare earth BR), etc. These may be used alone or in combination of two or more.

[0092] Among them, BR preferably contains high cis BR having a cis content of more than 90% by mass. The cis content is more preferably more than 95% by mass, and more preferably 98% by mass or more. The cis content can be measured by the above method.

[0093] In addition, BR may be unmodified BR or modified BR. Examples of modified BR include modified BR introduced with the same functional group as the modified diene rubber. In addition, hydrogenated butadiene polymer (hydrogenated BR) may be used as BR.

[0094] As BR, for example, products produced by Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Nippon Zeon Corporation, etc. can be used.

[0095] From the viewpoint of low fuel consumption and crack growth resistance, the BR content in 100% by mass of the rubber component is preferably greater than 20% by mass, more preferably greater than 25% by mass, further preferably greater than 30% by mass, further preferably greater than 35% by mass, further preferably greater than 40% by mass, further preferably greater than 45% by mass, further preferably greater than 50% by mass, further preferably greater than 55% by mass. On the other hand, the upper limit is preferably less than 75% by mass, more preferably less than 70% by mass, further preferably less than 65% by mass.

[0096] <<Other rubber components>> As the rubber component, rubbers other than the above can be used. As rubbers other than the above, diene rubbers such as styrene isoprene butadiene rubber (SIBR), chloroprene rubber (CR), acrylonitrile-butadiene rubber (NBR), and non-diene rubbers such as ethylene-propylene-diene rubber (EPDM), butyl rubber (IIR), and halogenated butyl rubber (X-IIR) can be listed. These can be used alone or in combination of two or more.

[0097] The content of the diene rubber in 100% by mass of the rubber component is preferably more than 80% by mass, more preferably more than 90% by mass, and most preferably 100% by mass.

[0098] (Bulking Agent) The rubber composition of the present invention preferably contains at least one of silica and carbon black (CB). In addition, the carbon black preferably contains recycled carbon black (rCB).

[0099] <<Silicon Dioxide>> As silicon dioxide, dry process silicon dioxide (anhydrous silicon dioxide), wet process silicon dioxide (hydrous silicon dioxide) and the like can be used. Among them, wet process silicon dioxide is preferred because of the large number of silanol groups. As commercially available products, products of Degussa, Rhodia, Tosoh Silicon Chemical Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Co., Ltd. and the like can be used. These can be used alone or in combination of two or more. In addition, in addition to these silicon dioxides, silicon dioxide made from biomass materials such as rice husks as raw materials can also be used.

[0100] The nitrogen adsorption specific surface area of ​​silicon dioxide (N 2 SA) is preferably greater than 50m 2 / g, more preferably greater than 100m 2 / g, more preferably 150m 2 / g or more, more preferably 175m 2 / g or more. N of silicon dioxide 2 The upper limit of SA is not particularly limited, but is preferably less than 600 m 2 / g, more preferably less than 350m 2 / g, more preferably less than 260m 2 / g. By keeping the content within the above range, the crack growth resistance tends to be improved. 2 SA is a value measured by the above-mentioned method.

[0101] From the viewpoint of reinforcement, low fuel consumption, etc., the average primary particle size of silica is preferably less than 25nm, more preferably less than 22nm, more preferably less than 20nm, and more preferably less than 18nm. Although the lower limit of the average primary particle size is not particularly limited, it is preferably greater than 3nm, more preferably greater than 5nm, and more preferably greater than 10nm. In addition, the average primary particle size of silica can be obtained by the above method.

[0102] The content of silica (total amount of silica) is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, more preferably less than 20 parts by mass, and more preferably less than 15 parts by mass relative to 100 parts by mass of the rubber component. On the other hand, the content is preferably greater than 1 part by mass, more preferably greater than 3 parts by mass, more preferably more than 5 parts by mass, and more preferably more than 10 parts by mass. It is believed that by properly reinforcing the rubber within the above range, the silica surfaces become easy to slide against each other, the elongation at break (EB) is improved, and the crack resistance can be easily improved.

[0103] <<Silane coupling agent>> When using silica, a silane coupling agent may be used in combination. However, in the present invention, even when silica is used, it is preferred not to use a silane coupling agent in combination. However, a silane coupling agent may be used as long as the effect of the present invention is not affected. The silane coupling agent is not particularly limited, and examples thereof include sulfide-based silane coupling agents such as bis(3-triethoxysilylpropyl) disulfide and bis(3-triethoxysilylpropyl) tetrasulfide; mercapto-based silane coupling agents such as 3-mercaptopropyltrimethoxysilane, NXT-Z100, NXT-Z45, and NXT (3-octanoylthiopropyltriethoxysilane) manufactured by Momentive; vinyl-based silane coupling agents such as vinyltriethoxysilane and vinyltrimethoxysilane; 3-aminopropyltriethoxysilane, 3-aminopropyltriethoxysilane; The silane coupling agent preferably comprises amino-based silane coupling agents such as propyltrimethoxysilane and 3-(2-aminoethyl)aminopropyltriethoxysilane; glycidoxy-based silane coupling agents such as γ-glycidoxypropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane; nitro-based silane coupling agents such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; chlorinated silane coupling agents such as 3-chloropropyltrimethoxysilane and 3-chloropropyltriethoxysilane, etc., preferably sulfide-based silane coupling agents and / or mercapto-based silane coupling agents, and particularly preferably mercapto-based silane coupling agents. These silane coupling agents may be used alone or in combination of two or more.

[0104] When a silane coupling agent is contained, from the viewpoint of improving the dispersibility of silica, the content relative to 100 parts by mass of silica (the total amount when multiple silane coupling agents are used in combination) is preferably greater than 1 part by mass, more preferably greater than 3 parts by mass, and further preferably greater than 5 parts by mass. In addition, the content is preferably less than 20 parts by mass, more preferably less than 15 parts by mass, further preferably less than 12 parts by mass, further preferably less than 9 parts by mass, and further preferably less than 7 parts by mass.

[0105] <<Carbon Black (CB)>> As carbon black, there is no particular limitation, and any one that can be used in the tire industry can be used. As such carbon black, for example, N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, N660, N762, etc. can be cited. As commercially available products, products of Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Co., Ltd., Lion Co., Ltd., Shin Nichia Carbon Co., Ltd., Columbia Carbon Black (Colombia Carbon) Co., Ltd., etc. can be used. In addition, from the viewpoint of environmental load, and from the viewpoint of reducing the friction between the carbon black surface and the rubber molecular chain and suppressing the heat generation, recycled carbon black (rCB) obtained from the thermal decomposition of used tires can also be used. These can be used alone, or two or more can be used in combination.

[0106] Recycled carbon black can be obtained by the thermal decomposition process of used pneumatic tires. For example, in the specification of European Patent Application Publication No. 3427975, it is mentioned that "Rubber Chemistry and Technology", Vo1.85, No.3, pages 408-449 (2012), especially pages 438, 440, and 442, record that it is obtained by thermal decomposition of organic materials at 550-800°C after excluding oxygen, or vacuum thermal decomposition at a relatively low temperature (

[0027] ). The carbon black obtained by such a thermal decomposition process is generally a substance lacking functional groups on its surface, as mentioned in

[0004] of Patent Gazette No. 6856781 (Comparison of the surface morphology and chemistry of thermally decomposed carbon black and commercially available carbon black, Powder Technology 160 (2005) 190-193).

[0107] The recovered carbon black is preferably a substance lacking functional groups on its surface, but as long as it does not affect the effect of the present invention, its surface may also contain functional groups. In addition, it may also be a substance that has been treated to make its surface contain functional groups. The treatment carried out to make the surface of the recovered carbon black contain functional groups can be implemented according to a common method. For example, in the specification of European Patent Application Publication No. 3173251, the carbon black obtained from the thermal decomposition process is treated with potassium permanganate under acidic conditions to obtain a carbon black containing hydroxyl and / or carboxyl groups on its surface. In addition, in the Japanese Patent Gazette No. 6856781, the carbon black obtained by the thermal decomposition process is treated with an amino acid compound containing at least one thiol group or disulfide group to obtain a carbon black activated on its surface. The recovered carbon black in the present embodiment also includes these carbon blacks that have been treated to make the surface contain functional groups.

[0108] As the recycled carbon black, commercially available products such as Strable Green Carbon and LD Carbon can be used.

[0109] The average primary particle size of carbon black is preferably greater than 20nm, more preferably greater than 25nm, further preferably greater than 30nm, and particularly preferably greater than 35nm. It is believed that by making the average primary particle size of carbon black within the above range, the rubber molecules bound by the carbon black are suppressed to a minimum, becoming easy to move flexibly, and even the input of polymer molecular chains can relieve stress, which can inhibit the occurrence of cracks. On the other hand, from the viewpoint of obtaining reinforcement, the average primary particle size is preferably less than 90nm, more preferably less than 75nm, and further preferably less than 65nm. In addition, the average primary particle size of carbon black is measured by the above-mentioned measurement method.

[0110] From the viewpoint of the effect of the present invention, the nitrogen adsorption specific surface area (N 2 SA) is preferably less than 90m 2 / g, more preferably less than 80m 2 / g, more preferably less than 70m 2 / g, particularly preferably less than 60m 2 / g. In addition, the N 2 SA is preferably greater than 10 m 2 / g, more preferably greater than 20m 2 / g, more preferably greater than 30m 2 / g, more preferably greater than 35m 2 / g, more preferably greater than 40m 2 / g. In addition, N 2 SA is measured by the above-mentioned measurement method.

[0111] From the viewpoint of obtaining reinforcement and preventing degradation caused by ultraviolet rays, when carbon black is contained, the content relative to 100 parts by mass of the rubber component is preferably greater than 1 part by mass, more preferably greater than 5 parts by mass, and further preferably 10 parts by mass or more. In addition, from the viewpoint of obtaining flexibility and relieving stress, the content is preferably less than 90 parts by mass, more preferably less than 70 parts by mass, further preferably less than 60 parts by mass, further preferably less than 50 parts by mass, and further preferably less than 40 parts by mass.

[0112] <<Formula (5)>> When the rubber composition of the present invention contains silica and carbon black, and assuming that the content (parts by mass) of silica per 100 parts by mass of the rubber component is S and the content (parts by mass) of carbon black is C, S and C preferably satisfy the following relationship. (5)S / C>0.50

[0113] The value on the right side of formula (5) is preferably 0.53, more preferably 0.55, further preferably 0.57, and further preferably 0.59. On the other hand, the value on the left side of formula (5) may be 1.00, 0.90, or 0.70.

[0114] <<Formula (6)>> When the rubber composition of the present invention contains silica and carbon black, and the carbon black contains recycled carbon black, when the content (mass parts) of silica relative to 100 parts by mass of the rubber component is S and the amount (mass parts) of recovered carbon black is rC, S and rC preferably satisfy the following relationship. (6)S / rC>1.00

[0115] The value of the right side of formula (6) is preferably 1.10, more preferably 1.15, further preferably 1.20, further preferably 1.25, further preferably 1.30. On the other hand, the value of the left side of formula (6) may be 2.00, 1.80, or 1.50.

[0116] <<Other fillers>> The tire rubber composition of the present invention may also contain other fillers besides silica and carbon black. Such other fillers are not particularly limited, and materials known in the rubber field can be used, such as inorganic fillers such as calcium carbonate, talc, alumina, clay, aluminum hydroxide, aluminum oxide, and mica.

[0117] <<Content of filler>> From the viewpoint of the effect of the present invention, the content of the filler (the total content of the filler) is preferably greater than 20 parts by mass, more preferably greater than 30 parts by mass, and more preferably 40 parts by mass or more relative to 100 parts by mass of the rubber component. The upper limit of the content is preferably less than 200 parts by mass, more preferably less than 150 parts by mass, more preferably less than 100 parts by mass, and more preferably less than 50 parts by mass.

[0118] (Other mixtures) In the rubber composition of the present invention, as other compounding agents, plasticizers, waxes, antioxidants, stearic acid, zinc oxide, vulcanizing agents, vulcanization accelerators, etc. can be used.

[0119] (Plasticizer) Plasticizer refers to a material that gives rubber plasticity, and is a concept that includes a plasticizer that is liquid (liquid) at room temperature (25°C) and a plasticizer that is solid at room temperature (25°C). Examples of plasticizers include oils, liquid polymers, ester plasticizers, etc. in addition to resins. The content of the plasticizer also includes the amount of the plasticizer in the rubber component increased by the plasticizer. One type of plasticizer can be used alone, or two or more types can be used in combination.

[0120] <<Resin>> The tire rubber composition of the present invention may contain resin. As the resin, petroleum resins, terpene resins, rosin resins, phenolic resins, etc. commonly used in the tire industry can be listed. These resin components can be used alone or in combination of two or more.

[0121] [Petroleum resin] Examples of the petroleum resin include C5-based petroleum resins, aromatic-based petroleum resins, and C5C9-based petroleum resins.

[0122] C5 petroleum resin refers to a resin obtained by polymerizing a C5 fraction, and may also be a hydrogenated product or a modified product thereof. Examples of C5 fractions include petroleum fractions corresponding to 4 to 5 carbon atoms such as cyclopentadiene, pentene, pentadiene, and isoprene. As C5 petroleum resin, dicyclopentadiene resin (DCPD resin) is preferably used.

[0123] Aromatic petroleum resin refers to a resin obtained by polymerizing a C9 fraction, and may also be a hydrogenated product or a modified product thereof. As the C9 fraction, for example, vinyl toluene, alkyl styrene, indene, methyl indene, etc., which are equivalent to petroleum fractions having 8 to 10 carbon atoms, may be cited. As specific examples of aromatic petroleum resins, for example, coumarone-indene resins, coumarone resins, indene resins, and aromatic vinyl resins may be suitably used. From the perspective of economy, ease of processing, and excellent heat generation, as aromatic vinyl resins, preferably homopolymers of α-methylstyrene or styrene, or copolymers of α-methylstyrene and styrene, more preferably copolymers of α-methylstyrene and styrene. As aromatic vinyl resins, commercially available substances such as Kraton and Eastman Chemical may be used.

[0124] C5C9 petroleum resin refers to a resin obtained by copolymerizing the above-mentioned C5 fraction and the above-mentioned C9 fraction, and may also be a hydrogenated product or a modified product thereof. As the C5 fraction and the C9 fraction, the above-mentioned petroleum fractions may be cited. As the C5C9 petroleum resin, for example, commercially available materials such as those produced by Tosoh Corporation and LUHUA Corporation may be used.

[0125] [Terpene resin] Examples of terpene resins include: polyterpene resins composed of at least one terpene compound selected from α-pinene, β-pinene, limonene, dipentene, etc.; aromatic modified terpene resins using the above terpene compounds and aromatic compounds as raw materials; terpene phenol resins using terpene compounds and phenol compounds as raw materials; and products obtained by hydrogenating these terpene resins (hydrogenated terpene resins). Examples of aromatic compounds that are raw materials for aromatic modified terpene resins include styrene, α-methylstyrene, vinyltoluene, divinyltoluene, etc. Examples of phenol compounds that are raw materials for terpene phenol resins include phenol, bisphenol A, cresol, xylenol, etc.

[0126] [Rosin-based resin] The rosin-based resin is not particularly limited, and examples thereof include natural resin rosin and rosin-modified resins obtained by modifying the rosin by hydrogenation, disproportionation, dimerization, esterification, or the like.

[0127] [Phenolic resin] The phenolic resin is not particularly limited, and examples thereof include phenolic resins, alkylphenolic resins, alkylphenolacetylene resins, and oil-modified phenolic resins.

[0128] [Resin content] The content of the resin component relative to 100 parts by mass of the rubber component is preferably greater than 1 part by mass, more preferably greater than 3 parts by mass, further preferably greater than 4 parts by mass, further preferably greater than 5 parts by mass. In addition, the content of the resin component is preferably less than 30 parts by mass, more preferably less than 25 parts by mass, further preferably less than 20 parts by mass.

[0129] <<Oil>> As the oil, for example, process oil, vegetable oil, animal oil, etc. can be cited. As the above-mentioned process oil, paraffin-based process oil, cycloparaffin-based process oil, aromatic-based process oil, etc. can be cited. In addition, due to environmental measures, process oils with a low content of polycyclic aromatic compounds (PCA) can also be used. As the above-mentioned process oils with low PCA content, mild extraction solvates (MES), treated distillate aromatic extracts (TDAE), heavy cycloparaffin-based oils, etc. can be cited. In addition, from the perspective of life cycle assessment, oils purified from waste oils used in rubber mixers or engines and waste cooking oils used in restaurants can also be used. One type of oil can be used alone, or two or more types can be used in combination.

[0130] <<Liquid Polymer>> The liquid polymer is not particularly limited as long as it is a polymer that is liquid at room temperature (25° C.), and examples thereof include liquid butadiene rubber (liquid BR), liquid styrene-butadiene rubber (liquid SBR), liquid isoprene rubber (liquid IR), liquid styrene isoprene rubber (liquid SIR), liquid farnesene rubber, etc. The liquid polymer may be used alone or in combination of two or more.

[0131] <<Ester plasticizer>> Examples of the ester plasticizer include dibutyl adipate (DBA), diisobutyl adipate (DIBA), dioctyl adipate (DOA), di(2-ethylhexyl) azelate (DOZ), dibutyl sebacate (DBS), diisononyl adipate (DINA), diethyl phthalate (DEP), dioctyl phthalate (DOP), diundecyl phthalate (DUP), dibutyl phthalate (DBP), dioctyl sebacate (DOS), tributyl phosphate (TBP), trioctyl phosphate (TOP), triethyl phosphate (TEP), trimethyl phosphate (TMP), thymidine triphosphate (TTP), tricresyl phosphate (TCP), and tri(xylene) phosphate (TXP). The ester plasticizer may be used alone or in combination of two or more.

[0132] <<Content of plasticizer other than resin>> When a plasticizer other than a resin is contained, the content relative to 100 parts by mass of the rubber component (the total amount when multiple parts are used) is preferably greater than 1 part by mass, more preferably greater than 2 parts by mass, and even more preferably greater than 3 parts by mass. In addition, the content of the plasticizer is preferably less than 50 parts by mass, more preferably less than 40 parts by mass, and even more preferably less than 30 parts by mass.

[0133] <<Wax>> The wax is not particularly limited, and any wax commonly used in the tire industry can be suitably used, for example, petroleum wax, mineral wax, synthetic wax, etc. Among them, petroleum wax is preferred. Examples of petroleum wax include paraffin wax, microcrystalline wax, and selected special waxes of these waxes, among which paraffin wax is preferred. For example, the wax can be manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seira Co., Ltd., and PARAMELT Co., Ltd. One wax or a combination of two or more waxes can be used.

[0134] When wax is contained, the content is preferably greater than 0.3 parts by mass, more preferably greater than 0.5 parts by mass, and further preferably greater than 1.0 parts by mass relative to 100 parts by mass of the rubber component. On the other hand, the content is preferably less than 4.0 parts by mass, more preferably less than 3.0 parts by mass, and further preferably less than 2.0 parts by mass.

[0135] <<Antiaging Agent>> As antioxidant, there is no particular limitation, and any kind commonly used in the tire industry can be suitably used. As antioxidant, for example, quinoline antioxidant, quinone antioxidant, phenol antioxidant, phenylenediamine antioxidant, and metal carbamate can be cited. Among them, phenylenediamine antioxidant is preferred because it can better exert the effect of improving ozone resistance.

[0136] When an antioxidant is contained, the content relative to 100 parts by mass of the rubber component is preferably greater than 0.5 parts by mass, more preferably greater than 1.0 parts by mass, and further preferably greater than 2.0 parts by mass. On the other hand, the content is preferably less than 7.0 parts by mass, more preferably less than 6.0 parts by mass, and further preferably less than 5.0 parts by mass.

[0137] <<Stearic Acid>> From the viewpoint of processability, when stearic acid is contained, the content relative to 100 parts by mass of the rubber component is preferably greater than 0.5 parts by mass, more preferably greater than 0.7 parts by mass, and even more preferably 1.0 parts by mass. On the other hand, from the viewpoint of vulcanization speed, the content is preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and even more preferably less than 3 parts by mass.

[0138] <<Zinc Oxide>> From the viewpoint of processability, when zinc oxide is contained, the content is preferably greater than 0.5 parts by mass, more preferably greater than 0.7 parts by mass, and even more preferably 1 part by mass or more relative to 100 parts by mass of the rubber component. On the other hand, from the viewpoint of friction resistance, the content is preferably less than 10 parts by mass, more preferably less than 7 parts by mass, and even more preferably less than 5 parts by mass.

[0139] <<Vulcanizing Agent>> The vulcanizing agent is not particularly limited, and known vulcanizing agents can be used, and examples thereof include organic peroxides, sulfur-based vulcanizing agents, resin vulcanizing agents, metal oxides such as magnesium oxide, etc. Among them, sulfur-based vulcanizing agents are preferred. As the sulfur-based vulcanizing agent, sulfur donors such as sulfur and morpholine disulfide can be used. Among these, sulfur is preferably used. The vulcanizing agent can be used alone or in combination of two or more.

[0140] Sulfur includes powdered sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur (oil-treated sulfur, special sulfur treated with a dispersant, masterbatch sulfur, etc.), insoluble sulfur (oil-treated insoluble sulfur, etc.), and the like, and any one of them can be used appropriately. Among them, powdered sulfur and insoluble sulfur are preferred. Sulfur manufactured and sold by Tsurumi Chemical Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Co., Ltd., Nippon Dry Industry Co., Ltd., Hosoi Chemical Co., Ltd., etc. can be used.

[0141] When containing a vulcanizing agent, the content relative to 100 parts by mass of the rubber component is preferably greater than 0.4 parts by mass, more preferably greater than 0.7 parts by mass, further preferably more than 1.0 parts by mass, and further preferably greater than 1.3 parts by mass. On the other hand, the content is preferably less than 6.0 parts by mass, more preferably less than 5.0 parts by mass, and further preferably less than 3.0 parts by mass. When the content of the vulcanizing agent is within the above range, it tends to obtain a suitable reinforcement effect, and tends to be able to better exert the effect of the present invention. In addition, when the vulcanizing agent contains components other than sulfur such as oil-treated sulfur, the content of the vulcanizing agent refers to the content of the sulfur component itself.

[0142] <<Vulcanization accelerator>> As the vulcanization accelerator, there is no particular limitation, and known vulcanization accelerators can be used, such as sulfenamide, thiazole, thiuram, thiourea, guanidine, dithiocarbamic acid, aldehyde-amine or aldehyde-ammonia, imidazoline, or xanthate vulcanization accelerators. Among them, sulfenamide, thiuram, and guanidine are preferred, and sulfenamide is more preferred. The vulcanization accelerator can use substances manufactured and sold by Ouchi Shinko Chemical Industry Co., Ltd., Sanshin Chemical Industry Co., Ltd., etc. These vulcanization accelerators can be used in one or in combination of two or more.

[0143] Examples of sulfenamide-based vulcanization accelerators include N-tert-butyl-2-benzothiazolylsulfenamide (TBBS), N-cyclohexyl-2-benzothiazolylsulfenamide (CBS), and N,N'-dicyclohexyl-2-benzothiazolylsulfenamide (DZ). Examples of thiuram-based vulcanization accelerators include tetramethylthiuram monosulfide, tetramethylthiuram disulfide, and tetrabenzylthiuram disulfide (TBzTD). Examples of guanidine-based vulcanization accelerators include 1,3-diphenylguanidine (DPG), di-o-tolylguanidine, and o-tolylbiguanide.

[0144] The content of the vulcanization accelerator is preferably greater than 0.3 parts by mass, more preferably greater than 0.5 parts by mass, and further preferably greater than 0.6 parts by mass relative to 100 parts by mass of the rubber component. On the other hand, the content is preferably less than 8.0 parts by mass, more preferably less than 5.0 parts by mass, and further preferably less than 4.0 parts by mass. When the content of the vulcanization accelerator is within the above range, the breaking strength and elongation tend to be ensured, and the effect of the present invention tends to be more well exerted.

[0145] <Manufacturing> The rubber composition of the present invention can be produced by a known method, for example, by kneading the above components using a rubber kneading device such as an open roll mill or a closed mixer (Banbury mixer, kneader, etc.).

[0146] The kneading process includes, for example, a basic kneading process for kneading a compounding agent and an additive other than a vulcanizing agent and a vulcanization accelerator, and a final kneading (F kneading) process for adding a vulcanizing agent and a vulcanization accelerator to the kneaded product obtained in the basic kneading process and kneading. Furthermore, the basic kneading process can be divided into a plurality of processes as required.

[0147] The kneading conditions are not particularly limited, but examples thereof include kneading at a discharge temperature of 150 to 170° C. for 3 to 10 minutes in the basic kneading step and kneading at 70 to 110° C. for 1 to 5 minutes in the final kneading step.

[0148] The tire of the present invention can be manufactured by conventional methods using the above-mentioned rubber composition. That is, the unvulcanized rubber composition in which the above-mentioned components are mixed as required with respect to the rubber component can be extruded in an extruder with a metal cover of a specified shape in accordance with the shape of the tire sidewall, and the unvulcanized tire sidewall obtained in this way and the bead apex rubber of the specified H and the bead reinforcing layer as required are laminated with other tire components in a tire molding machine, and molded by conventional methods to form an unvulcanized tire, and the unvulcanized tire is manufactured by heating and pressurizing the unvulcanized tire in a vulcanizer. The vulcanization conditions are not particularly limited, and for example, a method of vulcanizing at 150 to 200° C. for 10 to 30 minutes can be cited.

[0149] <Purpose> As tires, pneumatic tires and non-pneumatic tires can be listed. Among them, pneumatic tires are preferred. The tire can be used for passenger car tires, large passenger car tires, large SUV tires, heavy-duty tires such as trucks and buses, light truck tires, two-wheeled motor vehicle tires, racing tires (high-performance tires), etc. Among them, it can be suitably used for passenger car tires. Here, passenger car tires are tires that are loaded on a four-wheeled motor vehicle as a prerequisite, and refer to tires with a maximum load capacity WL of less than 1400kg. [Example]

[0150] Examples (Examples) considered to be preferable in practice are shown below, but the scope of the present invention is not limited to the Examples. The tires obtained according to the tables were examined using the various reagents shown below, and the results calculated based on the following evaluation methods are shown in the tables.

[0151] <Various medicines> The following is a summary of the reagents used in the Examples and Comparative Examples.

[0152] IR rubber: natural rubber (TSR20) BR: UBEPOL BR150B manufactured by Ube Industries, Ltd. (cis content: 98% by mass, vinyl bond content: 1% by mass) SBR: HPR840 manufactured by ENEOS Materials Co., Ltd. (styrene content: 10.0 mass %, vinyl bond content: 42.0 mol %) CB (Carbon Black) 1: SHOBLACK N550 (N 2 SA: 42m 2 / g, average primary particle size 48nm) CB (Carbon Black) 2: SHOBLACK N660 (N 2 SA: 35m 2 / g, average primary particle size 80nm) rCB (recycled carbon black): carbon black obtained by thermal decomposition of tires (ash content: 17% by mass) Silicon dioxide: ULTRASIL VN3 (N 2 SA 175m 2 / g, average primary particle size 17nm) Wax: OZOACE Wax manufactured by Nippon Seiro Co., Ltd. Antioxidant 1: NOCRAC 6C (N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Ouchi Shinko Chemical Co., Ltd. Antioxidant 2: NOCRAC RD (poly(2,2,4-trimethyl-1,2-dihydroquinoline)) manufactured by Ouchi Shinko Chemical Co., Ltd. Oil: Diana Process NH-70S (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. Zinc oxide: Zinc Hua No. 1 manufactured by Mitsui Mining and Smelting Co., Ltd. Stearic acid: TSUBAKI stearic acid beads manufactured by NOF Corporation Sulfur: SEIMIOT (10% oil-insoluble sulfur) manufactured by Nippon Kanryu Industry Co., Ltd. Vulcanization accelerator: NOCCELER CZ (N-cyclohexyl-2-benzothiazolylsulfenamide (CBS)) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0153] <Production of Unvulcanized Rubber Composition> According to the formulations shown in Tables 2-1 and 2-2 (collectively referred to as Table 2) and Tables 3-1 and 3-2 (collectively referred to as Table 3), a kneaded product was obtained by kneading for 5 minutes using a 1.7L closed Banbury mixer until the discharge temperature of the reagents other than sulfur and the vulcanization accelerator reached 170°C. Then, sulfur and the vulcanization accelerator were added to the obtained kneaded product using a biaxial open roll mill, and kneaded for 4 minutes until the temperature reached 105°C to obtain an unvulcanized rubber composition.

[0154] <Manufacturing of Test Tires> According to Tables 2 and 3, the obtained unvulcanized rubber composition was extruded into the shape of a sidewall using an extruder equipped with a metal cover of a specified shape, and the unvulcanized sidewall thus obtained was bonded together with a bead apex rubber having a specified H in a tire molding machine with other tire components to form an unvulcanized tire, and each test tire (Tire 1: 265 / 70R18, Tire 2: 205 / 55R16) was manufactured by press vulcanization at 170°C for 12 minutes.

[0155] In addition, the micro-ridges on the outer surface of the sidewall are formed during press vulcanization using a mold of a side plate having an imprint for forming the micro-ridges engraved on the opposite surface of the micro-ridge forming portion. The shapes of the micro-ridges A and B are shown below. In addition, the height h (mm) is the height of the micro-ridges at the maximum width position of the tire, the height h1 (mm) is the height of the micro-ridges at the outermost position in the radial direction of the tire, and the height h2 (mm) is the height of the micro-ridges at the innermost position in the radial direction of the tire. When the value of h1 is larger than h, the height of the micro-ridges increases gradually from the maximum width position of the tire to the outer side in the radial direction of the tire, and when the value of h2 is larger than h, the height of the micro-ridges increases gradually from the maximum width position of the tire to the inner side in the radial direction of the tire.

[0156]

Table 1

[0157] <70℃tanδ、70℃E*> From the inner side of the sidewall of each test tire, a rubber test piece for viscoelasticity measurement with a length of 20 mm, a width of 4 mm, and a thickness of 1 mm was cut with the tangent direction of the tire circumference as the long side and the tire width direction as the thickness. For each rubber test piece, the EPLEXOR series manufactured by GABO was used to measure the loss tangent (70°C tanδ) and the complex elastic modulus (70°C E*) (MPa) in the tensile deformation mode under the conditions of measuring temperature: 70°C, initial strain: 10%, dynamic strain: ±1%, and frequency: 10 Hz.

[0158] <Crack resistance> A 265 / 70R18 test tire was mounted on a 18×8.5J rim, and a 205 / 55R16 test tire was mounted on a 16×6.5J rim. Using a drum (outer diameter: 1.7 m), each test tire was subjected to a load and continuously driven for 40,000 km under the following conditions, and the total length of cracks in the sidewall generated after driving was calculated. Load: 4.74kN Internal pressure: 290kPa Speed: 100km / h

[0159] Based on the total length of the cracks, the crack resistance performance of each tire was expressed as an index using the following calculation formula, with the crack resistance performance index of the reference comparative example being 100. A larger index indicates better crack resistance performance. (Crack resistance index) = (crack length of the reference comparative example) / (crack length of each tire) × 100

[0160]

Table 2

[0161]

Table 3

[0162]

Table 4

[0163]

Table 5

[0164] <Implementation Method> Preferred embodiments are shown below.

[0165] [1] A tire comprising a pair of sidewalls and a pair of bead apex rubbers, wherein the loss tangent (tanδ) of a rubber composition constituting the sidewalls at 70°C is 70°C tanδ, the complex elastic modulus (MPa) of the rubber composition at 70°C is 70°C E*, the height (mm) of the bead apex rubber is H, the tire weight (kg) of the tire is G, and the maximum load capacity (kg) of the tire is WL, then 70°C tanδ, 70°C E*, H, G and WL satisfy the following relationship, wherein the right side of formula (1) is preferably 0.323, the right side of formula (2) is preferably 9.0, more preferably 8.0, and even more preferably 7.0, and the right side of formula (3) is preferably 0.0170. (1) 0.006×H-70℃tanδ>0.320 (2) 70℃E*<10.0 (3)G / WL<0.0180 [2] The tire according to [1] above, wherein when the thickness of the sidewall at the maximum width position of the tire is T (mm), 70°C E* and T satisfy the following relationship, and the right side of equation (4) is preferably 25.0, more preferably 20.0. (4) 70℃E*×T<31.5 [3] The tire according to [1] or [2], wherein the right side of the formula (1) is 0.328, preferably 0.329, more preferably 0.333, and even more preferably 0.339. [4] The tire according to any one of [1] to [3] above, wherein the right side of formula (2) is 6.0, more preferably 5.5, more preferably 4.5, more preferably 4.0, more preferably 3.8, more preferably 3.5, and more preferably 3.0. [5] The tire according to any one of [1] to [4] above, wherein the right side of the formula (3) is 0.0165, more preferably 0.0161. [6] The tire according to any one of [2] to [5] above, wherein the right side of the formula (4) is 16.0, more preferably 15.0, further preferably 14.0, further preferably 13.0, further preferably 12.0. [7] The tire according to any one of [1] to [6] above, wherein the rubber composition contains silica. [8] The tire according to any one of [1] to [7] above, wherein the rubber composition contains carbon black, and the carbon black contains recycled carbon black. [9] The tire according to any one of [1] to [6] above, wherein the rubber composition contains silica and carbon black. Relative to 100 parts by mass of the rubber component, assuming that the amount (parts by mass) of the silica is S and the amount (parts by mass) of the carbon black is C, S and C satisfy the following relationship: the right side of formula (5) is preferably 0.53, more preferably 0.55, further preferably 0.57, and further preferably 0.59. (5)S / C>0.50

[10] The tire according to any one of [1] to [6] above, wherein the rubber composition contains silica and carbon black, and the carbon black contains recycled carbon black. Relative to 100 parts by mass of the rubber component, assuming that the amount (parts by mass) of the silica is S, and the amount (parts by mass) of the recovered carbon black is rC, S and rC satisfy the following relationship, and the right side of formula (6) is preferably 1.10, more preferably 1.15, further preferably 1.20, further preferably 1.25, and further preferably 1.30. (6)S / rC>1.00

[11] The tire according to any one of [1] to

[10] above, wherein at least one of the pair of sidewalls has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface.

[12] The tire according to

[11] above, wherein the shape of the micro-ridges is columnar, conical, or rib-like.

[13] The tire according to

[11] or

[12] , wherein the height of the micro-ridges is 0.03 mm or more and 0.50 mm or less, preferably 0.05 mm or more and 0.45 mm or less, and more preferably 0.10 mm or more and 0.40 mm or less, and 20 or more micro-ridges are formed at intervals of 0.50 mm or less in at least one direction, and the micro-ridge forming portion has a 10 mm 2 The area above.

[14] A tire according to any one of

[11] to

[13] above, wherein the maximum width of the micro-ridges is greater than or equal to 0.03 mm and less than or equal to 5.0 mm, preferably greater than or equal to 0.05 mm and less than or equal to 3.0 mm, and more preferably greater than or equal to 0.10 mm and less than or equal to 1.0 mm.

[15] A tire according to any one of

[11] to

[14] above, wherein the height of the micro-ridges increases gradually from the maximum width position of the tire toward the outer side in the tire radial direction, and gradually increases from the maximum width position of the tire toward the inner side in the tire radial direction.< / sbr>

Claims

1. A tire having a pair of sidewalls and a pair of bead apex rubbers, Assuming that the loss tangent tanδ of the rubber composition constituting the sidewall at 70°C is 70°C tanδ, the complex elastic modulus of the rubber composition at 70°C is 70°C E*, the unit of the complex elastic modulus is MPa, the height of the bead apex rubber is H, the unit of the height is mm, the tire weight of the tire is G, the unit of the tire weight is kg, and the maximum load capacity of the tire is WL, the unit of the maximum load capacity is kg, 70°C tanδ, 70°C E*, H, G and WL satisfy the following relationship, (1) 0.006×H-70℃tanδ>0.320 (2)70℃E*<10.0 (3)G / WL<0.0180.

2. The tire according to claim 1, wherein: Assuming that the thickness of the sidewall of the tire at the maximum width position is T, and the unit of the thickness is mm, 70°E* and T satisfy the following relationship, (4)70℃E*×T<31.

5.

3. The tire according to claim 1, wherein: The value of the right side of formula (1) is 0.

328.

4. The tire according to claim 1, wherein: The value of the right side of formula (2) is 6.

0.

5. The tire according to claim 1, wherein: The value on the right side of formula (3) is 0.0165.

6. The tire according to claim 2, wherein: The value of the right side of formula (4) is 16.

0.

7. The tire according to any one of claims 1 to 6, wherein The rubber composition contains silica.

8. The tire according to any one of claims 1 to 6, wherein The rubber composition contains carbon black, and the carbon black contains recycled carbon black.

9. The tire according to any one of claims 1 to 6, wherein: The rubber composition contains silica and carbon black, Assuming that the content of the silica is S and the content of the carbon black is C relative to 100 parts by mass of the rubber component, S and C satisfy the following relationship, and the units of the content of the silica and the content of the carbon black are parts by mass, (5)S / C>0.

50.

10. The tire according to any one of claims 1 to 6, wherein The rubber composition contains silica and carbon black, wherein the carbon black contains recycled carbon black. Assuming that the content of the silica is S and the content of the recovered carbon black is rC relative to 100 parts by mass of the rubber component, S and rC satisfy the following relationship, and the units of the content of the silica and the content of the recovered carbon black are parts by mass, (6)S / rC>1.

00.

11. The tire according to claim 1, wherein: At least one of the pair of sidewalls has a micro-ridge forming portion having a plurality of micro-ridges formed on an outer surface.

12. The tire according to claim 11, wherein: The micro protrusions are in the shape of columns, truncated cones or ribs.

13. The tire according to claim 11 or 12, wherein: The height of the micro-ridges is 0.03 mm or more and 0.50 mm or less, and 20 or more micro-ridges are formed at intervals of 0.50 mm or less in at least one direction. The micro-ridge forming portion has a 10 mm 2 The area above.

14. The tire according to claim 11 or 12, wherein: The maximum width of the micro-ridges is not less than 0.03 mm and not more than 5.0 mm.

15. The tire according to claim 11 or 12, wherein: The height of the micro-ridges gradually increases from the maximum width position of the tire toward the outer side in the tire radial direction, and gradually increases from the maximum width position of the tire toward the inner side in the tire radial direction.